2015
DOI: 10.1016/j.celrep.2015.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Ebola Virus Escape Variants in Infected Nonhuman Primates Treated with the MB-003 Antibody Cocktail

Abstract: MB-003, a plant-derived monoclonal antibody cocktail used effectively in treatment of Ebola virus infection in non-human primates, was unable to protect two of six animals when initiated 1 or 2 days post-infection. We characterized a mechanism of viral escape in one of the animals, after observation of two clusters of genomic mutations that resulted in five nonsynonymous mutations in the monoclonal antibody target sites. These mutations were linked to a reduction in antibody binding and later confirmed to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…In this study, animals were given MB-003 on days 4, 7 and 10 after EBOV infection; three of the seven treated animals survived. Interestingly, evaluation of the two surviving animals from the Olinger et al study 139 identified the emergence of escape mutants in the two animals that did not survive EBOV challenge 141 .…”
mentioning
confidence: 99%
“…In this study, animals were given MB-003 on days 4, 7 and 10 after EBOV infection; three of the seven treated animals survived. Interestingly, evaluation of the two surviving animals from the Olinger et al study 139 identified the emergence of escape mutants in the two animals that did not survive EBOV challenge 141 .…”
mentioning
confidence: 99%
“…The most potently neutralizing and therapeutically effective mAbs in our panel target the GP1/GP2 interface and the GP stalk region, suggesting that these epitopes may be promising targets for rational vaccine design. In addition, the observation that EBOV escape variants can emerge after treatment with the MB-003 antibody cocktail highlights the need for protective mAbs that target new antigenic sites, such as those described here targeting the GP stalk (25, 26). …”
mentioning
confidence: 98%
“…For example, coupled with another therapy (interferon, for example, as used in combination with ribavirin for hepatitis C virus [HCV] therapy) or administered while a patient awaits experimental therapies (such as Zmapp [44]), the decrease in viral load should enhance the efficacy of other treatments and lead to improved outcomes; decreased viral loads have previously been associated with survival (45,46). Inclusion of a mutagen, such as ribavirin, may also be beneficial when administering certain therapies, such as antibody cocktails (47), that may suffer from antiviral resistance. Furthermore, it is critical to consider that these studies were not performed in the context of supportive care and rehydration, which can be instrumental in improving outcomes for human infections (48).…”
Section: Effect Of Prophylactic Ribavirin On Ebola Virus Infection Inmentioning
confidence: 99%